(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the epidemiological profile of leprosy in the state of Maranhão. Retrospective cross-sectional study of leprosy cases from 2018 to 2020 in the state of Maranhão, northeastern Brazil. Data were obtained through consultations in the database of the Information System for Notifiable Diseases (SINAN), available at the Information Technology Department of the Unified Health System (DATASUS). The variables used in the study were: health macroregions, gender, education and clinical form. Between 2018 and 2020, according to DATASUS, 10,776 cases of leprosy were reported in Maranhão, with an average of 3592 cases/year. In 2018, 4,195 cases were reported, compared to 2020 with 2,316 cases, with the lowest number of cases in the last 3 years. In the present study, it was observed that leprosy was predominant in males, in the Northern macro-region, in people of the mixed race, in people with low educational level, and the most common clinical form was borderline. Social conditions and vulnerability associate leprosy with precarious situations of hygiene and low economic status, leading to difficulty in accessing health care. It is expected, therefore, that state and municipal health agencies promote access to health information for the affected population, actions that promote improvement of disease control indicators in Maranhão, aiming to improve aspects related to education and health, having greater attention to the male public, so that the treatment of the disease occurs efficiently.